Solid catalyst component for olefin polymerization, production method of solid catalyst component for olefin polymerization, catalyst for olefin polymerization, and production method of olefin polymer

JP2025020611APending Publication Date: 2025-02-13TOHO TITANIUM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023124097
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、フタル酸エステル以外の内部電子供与性化合物を含み、溶融流れ性に優れるとともに剛性が高く、且つ、低分子量の重合体が少ないオレフィン類重合体を製造し得るオレフィン類重合用固体触媒成分を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020611000004
    Figure 2025020611000004
  • Figure 2025020611000005
    Figure 2025020611000005
  • Figure 2025020611000006
    Figure 2025020611000006
Patent Text Reader

Abstract

To provide a solid catalyst component for olefin polymerization capable of producing an olefin polymer containing an inner electron donative compound excluding a phthalic acid ester, excellent in melt flowability, high in rigidity, and small in a low molecular weight polymer.SOLUTION: A solid catalyst component for olefin polymerization has a total of a content of a 1,3-diether compound having no olefin structure and a content of a succinic acid diester compound in the whole component amount in terms of a solid content of 13.0 mass% or more, a mole ratio (S / T) expressed by a molar content (S) of a succinic acid diester compound to a molar content (T) of titanium of 0.71 to 1.30, a mole ratio (E / S) expressed by a molar content (E) of a 1,3-diether compound having no fluorene structure to a molar content (S) of a succinic acid diester compound of 0.10 to 0.70, a total pore volume having a diameter of 1 μm or less of 0.3 to 1.0 cm3 / g, and a specific surface area of 200 m2 / g or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid catalyst component for olefin polymerization, a method for producing a solid catalyst component for olefin polymerization, a catalyst for olefin polymerization, a method for producing an olefin polymer, and an olefin polymer. [Background technology]

[0002] In recent years, olefin polymers such as polypropylene (PP) have been used for a variety of applications, including molded products such as automobile parts and home appliances, as well as containers and films.

[0003] Polypropylene-based resin compositions are lightweight and have excellent moldability, and also provide molded articles with excellent chemical stability such as heat resistance and chemical resistance, and are also very cost-effective. Therefore, they are used in many fields as one of the most important plastic materials.

[0004] To further expand its applications, there is a demand for polypropylene that can be used as a replacement for polystyrene and ABS resin, has low levels of low molecular weight components and amorphous polymers, has high melt flow properties (melt flow rate (MFR)), is excellent in moldability, and has high rigidity.

[0005] In the polymerization of olefins such as propylene, a polymerization method using a solid catalyst component containing, as essential components, a magnesium atom, a titanium atom, a halogen atom, and an internal electron donor compound is known, and many methods have been proposed for polymerizing or copolymerizing olefins in the presence of an olefin polymerization catalyst comprising the above-mentioned solid catalyst component, an organoaluminum compound, and an organosilicon compound.

[0006] For example, Patent Document 1 proposes a method for polymerizing propylene using an olefin polymerization catalyst that contains a solid titanium catalyst component supporting an internal electron donor compound such as a phthalate ester, and an organoaluminum compound and an organosilicon compound having at least one Si-O-C bond as co-catalyst components. Many documents, including Patent Document 1, propose methods for using a phthalate ester as an internal electron donor compound to obtain a highly stereoregular polymer under high polymerization activity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 57-63310 Summary of the Invention [Problem to be solved by the invention]

[0008] However, di-n-butyl phthalate and benzyl butyl phthalate, which are types of phthalate esters, have been identified as Substances of Very High Concern (SVHC) under the European Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) regulation, and there is an increasing demand to switch to catalyst systems that do not use SVHC substances in order to reduce the environmental impact.

[0009] Therefore, the present inventors have investigated a solid catalyst component for olefin polymerization containing an internal electron donor compound other than a phthalate ester and have found that by using a succinic acid diester compound as an internal electron donor compound, polypropylene having a high rigidity with a flexural modulus (FM) of 1,900 MPa or more can be obtained.

[0010] However, such polypropylene was found to have a low hydrogen response, making it difficult to produce polypropylene that combines high melt flowability (melt flow rate (MFR)) and high rigidity using a solid catalyst component for olefin polymerization that contains an internal electron donor compound other than phthalate ester.

[0011] In addition, the solid catalyst component for olefin polymerization using a succinic acid diester compound as an internal electron donor compound has a broad molecular weight distribution when used in the polymerization of olefins, and therefore contains a large amount of low molecular weight polymers, which adversely affect the physical properties and moldability of the polymer.

[0012] Under such circumstances, an object of the present invention is to provide a solid catalyst component for olefin polymerization which contains an internal electron donor compound other than a phthalic acid ester, has excellent melt flowability and high rigidity, and is capable of producing an olefin polymer containing a small amount of low-molecular-weight polymers. [Means for solving the problem]

[0013] In order to solve the above technical problems, the present inventors have conducted intensive research and have discovered that a 1,3-diether compound and a succinic acid diester compound, which are free of magnesium, titanium, halogen, and a fluorene structure, have a total pore volume of 0.3 to 1.0 cm3 having a diameter of 1 μm or less as measured by mercury intrusion porosimetry. 3 / g and the specific surface area is 200m 2The inventors have found that the above technical problems can be solved by a solid catalyst component for olefin polymerization having a solid content of 1,3-diether compound not having a fluorene structure and a succinic acid diester compound in the total amount of components of 13.0% by mass or more, when converted into solid content, a molar ratio (S / T) expressed by the molar amount (S) of the succinic acid diester compound in the total amount of components to the molar amount (T) of titanium of 0.71 to 1.30, and a molar ratio (E / S) expressed by the molar amount (E) of the 1,3-diether compound not having a fluorene structure to the molar amount (S) of the succinic acid diester compound of 0.10 to 0.70, and have completed the present invention based on this finding.

[0014] That is, the present invention provides (1) Magnesium, titanium, halogen, 1,3-diether compounds and succinic acid diester compounds that do not have a fluorene structure, When calculated as a solid content, the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of components is 13.0 mass% or more, a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound in the total amount of components to the molar amount (T) of the titanium in the total amount of components is 0.71 to 1.30; a molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure in the total amount of components relative to the molar amount (S) of the succinic acid diester compound in the total amount of components is 0.10 to 0.70; The total pore volume of pores with diameters of 1 μm or less measured by mercury intrusion porosimetry is 0.3 to 1.0 cm 3 / g and the specific surface area is 200m 2 / g or more, A solid catalyst component for olefin polymerization, comprising: (2) The 1,3-diether compound not having a fluorene structure is represented by the following general formula (1); R 1 -O-CH2-CR 2R 3 -CH2-OR 4 (1) (In the formula, R 2 and R 3 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group or a cycloalkenyl group having 3 to 12 carbon atoms, an aromatic hydrocarbon group or a halogen-substituted aromatic hydrocarbon group having 6 to 12 carbon atoms, an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent, an alkylamino group having 1 to 12 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms. R 2 and R 3 may be the same or different. 2 and R 3 may be bonded to each other to form a ring. 1 and R 4 R represents an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, a halogen-substituted aromatic hydrocarbon group, or an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent. 1 and R 4 may be the same or different.) 1. A solid catalyst component for olefin polymerization according to claim 1, which is characterized in that the solid catalyst component is at least one selected from 1,3-diether compounds represented by the following formula: (3) The succinic acid diester compound is represented by the following general formula (2); R 5 -OC(=O)-CHR 6 CHR 7 -C(=O)-OR 8 (2) (In the formula, R 6 and R 7 are hydrogen atoms or alkyl groups having 1 to 4 carbon atoms, and may be the same or different; R 5 and R 8 are straight-chain or branched alkyl groups having 2 to 4 carbon atoms, and may be the same or different.) The solid catalyst component for olefin polymerization according to claim 1, characterized in that the solid catalyst component is one or more compounds selected from the group consisting of compounds represented by the formula: (4) A method for producing a solid catalyst component for olefin polymerization according to any one of (1) to (3), comprising contacting a dialkoxymagnesium, a titanium halogen compound, a 1,3-diether compound not having a fluorene structure, and a succinic acid diester compound with each other, contacting the dialkoxymagnesium with the titanium halide compound multiple times; When the dialkoxymagnesium is initially contacted with the titanium halide compound, the amount of the titanium halide compound contacted is 1.5 to 10.0 mol per 1.0 mol of the dialkoxymagnesium, the total amount of the titanium halide compound used is 5.0 to 18.0 mol per 1.0 mol of the dialkoxymagnesium; the total molar amount of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound is 0.10 to 0.20 mol per 1.0 mol of the dialkoxymagnesium, a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound to the total molar amount (T) of the titanium halide compound is 0.020 to 0.040; a molar ratio (E / S) of the succinic acid diester compound to the 1,3-diether compound not having a fluorene structure (E) being 0.50 or less; The dialkoxymagnesium is composed of secondary particles that are aggregates of primary particles having an average particle diameter of less than 2 μm, and has a specific surface area of ​​10 m 2 / g or more 50m 2 / g and the particle size distribution index (SPAN) is 1.30 or less. A method for producing a solid catalyst component for olefin polymerization, comprising the steps of: (5) (I) A solid catalyst component for olefin polymerization according to any one of (1) to (3), and (II) the following general formula (3); R 9p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is 0. <p≦3であり、R 9 If there are multiple R 9 may be the same or different, and when there are multiple Qs, each Q may be the same or different. An organoaluminum compound represented by the formula: A catalyst for olefin polymerization comprising: (6) (I) A solid catalyst component for olefin polymerization according to any one of (1) to (3), (II) the following general formula (3); R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is 0. <p≦3であり、R 9 If there are multiple R 9 may be the same or different, and when there are multiple Qs, each Q may be the same or different. and an organoaluminum compound represented by (III) External electron donor compound The catalyst for olefin polymerization according to (5) above, (7) A process for producing olefin polymers, comprising carrying out polymerization of olefins using the olefin polymerization catalyst according to (5) or (6). This provides: Effect of the Invention

[0015] According to the present invention, there can be provided a solid catalyst component for olefin polymerization which contains an internal electron donor compound other than a phthalate ester, has excellent melt flowability and high rigidity, and is capable of producing an olefin polymer containing a small amount of low-molecular-weight polymers. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a diagram for explaining a method for preparing a measurement sample for measuring the proportion of an oriented layer in a cross section of an injection-molded plate of an olefin polymer. [Diagram 2] FIG. 2 is a diagram for explaining a method for preparing a measurement sample for measuring the proportion of an oriented layer in a cross section of an injection-molded plate of an olefin polymer. [Diagram 3] FIG. 13 is a diagram for explaining a method for specifying the proportion of an orientation layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] First, the solid catalyst component for olefin polymerization according to the present invention will be described. The solid catalyst component for olefin polymerization according to the present invention comprises: Contains 1,3-diether compounds and succinic acid diester compounds that do not contain magnesium, titanium, halogen, or a fluorene structure, When calculated as a solid content, the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of components is 13.0 mass% or more, a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound in the total amount of components to the molar amount (T) of the titanium in the total amount of components is 0.71 to 1.30; a molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure in the total amount of components relative to the molar amount (S) of the succinic acid diester compound in the total amount of components is 0.10 to 0.70; The total pore volume of pores with diameters of 1 μm or less measured by mercury intrusion porosimetry is 0.3 to 1.0 cm 3 / g and the specific surface area is 200m 2 / g or more, The present invention is characterized by the following:

[0018] The solid catalyst component for olefin polymerization according to the present invention may be a contact reaction product obtained by contacting and reacting a raw material component serving as a magnesium supply source, a raw material component serving as a titanium and halogen supply source, and an internal electron donor compound, i.e., a 1,3-diether compound not having a fluorene structure and a succinic acid diester compound, in an organic solvent. Specifically, a dialkoxymagnesium is used as a raw material component serving as a magnesium supply source, and a tetravalent titanium halogen compound is used as a raw material component serving as a titanium and halogen supply source, and these raw materials are contacted with an internal electron donor compound including a 1,3-diether compound not having a fluorene structure and a succinic acid diester compound.

[0019] In the solid catalyst component for olefin polymerization according to the present invention, specific examples of dialkoxymagnesium, which is a raw material component serving as a magnesium supply source, include dimethoxymagnesium, diethoxymagnesium, dipropoxymagnesium, dibutoxymagnesium, ethoxymethoxymagnesium, ethoxypropoxymagnesium, butoxyethoxymagnesium, and the like, with diethoxymagnesium being particularly preferred.

[0020] The dialkoxymagnesium may be one obtained by reacting metallic magnesium with an alcohol in the presence of a halogen or a halogen-containing metal compound.

[0021] The dialkoxymagnesium is preferably in the form of granules or powder, and the shape thereof may be irregular or spherical.

[0022] When a spherical dialkoxymagnesium is used, a polymer powder having a better particle shape (more spherical) and a narrow particle size distribution can be obtained, which improves the handleability of the polymer powder produced during the polymerization operation and makes it possible to suppress the occurrence of blockages and the like due to fine powder contained in the produced polymer powder.

[0023] The above-mentioned spherical dialkoxymagnesium particles do not necessarily have to be perfectly spherical, and elliptical or potato-shaped particles may also be used.

[0024] The average particle size (average particle size D50) of the dialkoxymagnesium is preferably 1.0 to 200.0 μm, and more preferably 5.0 to 150.0 μm, where the average particle size D50 refers to the particle size at 50% of the cumulative particle size in the volume cumulative particle size distribution measured using a laser light scattering diffraction particle size measuring device. When the dialkoxymagnesium is spherical, the average particle size D50 is preferably from 1.0 to 100.0 μm, more preferably from 5.0 to 80.0 μm, and even more preferably from 10.0 to 70.0 μm.

[0025] In addition, the dialkoxymagnesium preferably has a narrow particle size distribution with few fine and coarse particles. Specifically, when measured using a laser light scattering diffraction method particle size measuring instrument, the dialkoxymagnesium preferably has 20% or less, more preferably 10% or less, particles with a particle size of 5.0 μm or less, while when measured using a laser light scattering diffraction method particle size measuring instrument, the dialkoxymagnesium preferably has 20% or less, more preferably 10% or less, particles with a particle size of 100.0 μm or more, respectively. Furthermore, when the particle size distribution is expressed as ln(D90 / D10), it is preferably 3 or less, and more preferably 2 or less. Here, D90 means a particle size of 90% of the integrated particle size in the volume integrated particle size distribution when measured using a laser light scattering diffraction particle size measuring instrument. Also, D10 means a particle size of 10% of the integrated particle size in the volume integrated particle size distribution when measured using a laser light scattering diffraction particle size measuring instrument. Also, D50, which will be described later, means a particle size of 50% of the integrated particle size in the volume integrated particle size distribution when measured using a laser light scattering diffraction particle size measuring instrument.

[0026] Methods for producing the above-mentioned spherical dialkoxymagnesium are exemplified in, for example, JP-A Nos. 62-51633, 3-74341, 4-368391, and 8-73388.

[0027] In the solid catalyst component for olefin polymerization according to the present invention, the dialkoxymagnesium is preferably composed of secondary particles which are aggregates of primary particles having an average particle size of less than 2 μm. By using the above-mentioned dialkoxymagnesium, a solid catalyst component for olefin polymerization having a desired specific surface area and pore volume can be easily prepared.

[0028] In the solid catalyst component for olefin polymerization according to the present invention, the dialkoxymagnesium has a specific surface area of ​​10 m 2 / g or more 50m 2 / g or less, and 10 to 50m 2 / g is more preferable, and 10 to 40m 2 By using a dialkoxymagnesium having a specific surface area within the above range, a solid catalyst component for olefin polymerization having a desired specific surface area can be easily prepared.

[0029] In the solid catalyst component for olefin polymerization according to the present invention, the dialkoxymagnesium preferably has a particle size distribution index (SPAN=(D90-D10) / D50) of 1.30 or less, more preferably 0.60 to 1.00, and even more preferably 0.70 to 0.90, when measured using a laser light scattering diffraction particle size analyzer. By using a dialkoxymagnesium having a particle size distribution index (SPAN) within the above range, the handling operability of the polymer powder produced during the polymerization operation is improved, and the occurrence of blockages and the like due to fine powder contained in the produced polymer powder can be suppressed.

[0030] In the present invention, the fact that dialkoxymagnesium is composed of secondary particles which are aggregates of primary particles having an average particle diameter of less than 2 μm is confirmed by visual inspection of a negative photographed using a scanning electron microscope, the primary particle diameter is calculated by a statistical analysis method based on the longest diameter of at least 100 particles, and the secondary particle diameter is confirmed by measurement using a laser light scattering diffraction particle sizer.

[0031] In the present application, the specific surface area of ​​dialkoxymagnesium refers to a value measured by the BET method. Specifically, the specific surface area of ​​dialkoxymagnesium refers to a value measured by the BET method (automatic measurement) using an Automatic Surface Area Analyzer HM model-1230 manufactured by Mountech Co., Ltd., in the presence of a mixed gas of nitrogen and helium, after previously drying the measurement sample in vacuum at 50°C for 2 hours.

[0032] The dialkoxymagnesium is preferably in the form of a solution or suspension during the reaction, and being in the form of a solution or suspension allows the reaction to proceed favorably.

[0033] When the dialkoxymagnesium is a solid, it can be made into a dialkoxymagnesium solution by dissolving it in a solvent capable of solubilizing the dialkoxymagnesium, or it can be made into a dialkoxymagnesium suspension by suspending it in a solvent not capable of solubilizing the dialkoxymagnesium. When the dialkoxymagnesium is liquid, it may be used as it is in the form of a dialkoxymagnesium solution, or it may be further dissolved in a solvent capable of solubilizing the dialkoxymagnesium and used as a dialkoxymagnesium solution.

[0034] The compound capable of solubilizing solid dialkoxymagnesium includes at least one compound selected from the group consisting of alcohols, ethers, and esters. Alcohols such as ethanol, propanol, butanol, and 2-ethylhexanol are preferred, with 2-ethylhexanol being particularly preferred. On the other hand, examples of the medium that does not have the ability to solubilize solid dialkoxymagnesium include one or more solvents selected from saturated hydrocarbon solvents and unsaturated hydrocarbon solvents that do not dissolve dialkoxymagnesium.

[0035] In the solid catalyst component for olefin polymerization according to the present invention, the tetravalent titanium halogen compound, which is a raw material component serving as a supply source of titanium and halogen, is not particularly limited, and may be a compound represented by the following general formula (4): Ti(OR 10 ) r X 4-r (4) (In the formula, R 10 represents an alkyl group having 1 to 4 carbon atoms, X represents a halogen atom such as a chlorine atom, a bromine atom, or an iodine atom, and r is 0≦r≦3. It is preferable that the titanium halide or alkoxy titanium halide be one or more compounds selected from the group consisting of titanium halides and alkoxy titanium halides represented by the following formula:

[0036] In the above general formula (4), r is 0≦r≦3. Specifically, r is 0, 1, 2, or 3.

[0037] The titanium halide represented by the above general formula (4) may be one or more titanium tetrahalides selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, and the like. Examples of the alkoxytitanium halide represented by the above general formula (4) include one or more selected from methoxytitanium trichloride, ethoxytitanium trichloride, propoxytitanium trichloride, n-butoxytitanium trichloride, dimethoxytitanium dichloride, diethoxytitanium dichloride, dipropoxytitanium dichloride, di-n-butoxytitanium dichloride, trimethoxytitanium chloride, triethoxytitanium chloride, tripropoxytitanium chloride, tri-n-butoxytitanium chloride, and the like. As the tetravalent titanium halide compound, titanium tetrahalide is preferred, and titanium tetrachloride is more preferred. These titanium compounds may be used alone or in combination of two or more kinds.

[0038] In the solid catalyst component for olefin polymerization according to the present invention, the 1,3-diether compound having no fluorene structure refers to a compound having a structure in which atoms are bonded in the order of carbon atom-oxygen atom-carbon atom-carbon atom-carbon atom-oxygen atom-carbon atom and having no fluorene structure in the molecule.

[0039] Examples of the 1,3-diether compound not having a fluorene structure include those represented by the following general formula (1); R 1 -O-CH2-CR 2 R 3 -CH2-OR 4 (1) (In the formula, R 2 and R 3 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group or a cycloalkenyl group having 3 to 12 carbon atoms, an aromatic hydrocarbon group or a halogen-substituted aromatic hydrocarbon group having 6 to 12 carbon atoms, an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent, an alkylamino group having 1 to 12 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms. R 2 and R 3 may be the same or different. 2 and R3 may be bonded to each other to form a ring. 1 and R 4 R represents an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, a halogen-substituted aromatic hydrocarbon group, or an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent. 1 and R 4 may be the same or different.) Examples of the 1,3-diether compounds include one or more selected from the 1,3-diether compounds represented by the following formula:

[0040] In the 1,3-diether compound represented by the general formula (1), R 1 and R 4 are linear or branched alkyl groups having 1 to 4 carbon atoms, and may be the same or different. R 1 and R 4 Specific examples of the alkyl group that can be used include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group when the alkyl group is a linear or branched alkyl group having 1 to 4 carbon atoms.

[0041] In the 1,3-diether compound represented by the general formula (1), R 2 and R 3 are hydrogen atoms or alkyl groups having 2 to 5 carbon atoms, and may be the same or different. R 2 and R 3 Specifically, when the alkyl group is an alkyl group having 2 to 5 carbon atoms, specific examples thereof include an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group or an isobutyl group, an n-pentyl group, and an isopentyl group.

[0042] In the solid catalyst component for olefin polymerization according to the present invention, the 1,3-diether compound not having a fluorene structure is not particularly limited, and may be, for example, one or more selected from 2-isopropyl-2-isobutyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 2,2-dicyclohexyl-1,3-dimethoxypropane, 2,2-bis(cyclohexylmethyl)1,3-dimethoxypropane, etc., and among them, one or more selected from 2-isopropyl-2-isobutyl-1,3-dimethoxypropane, and 2-isopropyl-2-isopentyl-1,3-dimethoxypropane are preferred.

[0043] In the solid catalyst component for olefin polymerization according to the present invention, the succinic acid diester compound is represented by the following general formula (2): R 5 -OC(=O)-CHR 6 CHR 7 -C(=O)-OR 8 (2) (R 6 and R 7 are hydrogen atoms or alkyl groups having 1 to 4 carbon atoms, and may be the same or different; R 5 and R 8 are straight-chain or branched alkyl groups having 2 to 4 carbon atoms, and may be the same or different.) The compound may be one or more selected from the compounds represented by the following formula:

[0044] In the compound represented by the general formula (2), R 5 and R 8 are straight chain or branched alkyl groups having 2 to 4 carbon atoms and may be the same or different. R 5 and R 8 When is a linear or branched alkyl group having 2 to 4 carbon atoms, specific examples include an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group. In the compound represented by the general formula (2), R 6 and R 7 are hydrogen atoms or alkyl groups having 1 to 4 carbon atoms, and may be the same or different. R 6 and R 7 When is an alkyl group having 1 to 4 carbon atoms, specific examples include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group.

[0045] In the solid catalyst component for olefin polymerization according to the present invention, the succinic acid diester compound is not particularly limited and may be, for example, Diethyl succinate, diethyl 2,3-dimethylsuccinate, diethyl 2,3-diethylsuccinate, diethyl 2,3-di-n-propylsuccinate, diethyl 2,3-diisopropylsuccinate, diethyl 2,3-di-n-butylsuccinate, diethyl 2,3-diisobutylsuccinate; Di-n-propyl succinate, di-n-propyl 2,3-dimethyl succinate, di-n-propyl 2,3-diethyl succinate, di-n-propyl 2,3-di-n-propyl succinate, di-n-propyl 2,3-diisopropyl succinate, di-n-propyl 2,3-di-n-butyl succinate, di-n-propyl 2,3-diisobutyl succinate; Diisopropyl succinate, diisopropyl 2,3-dimethyl succinate, diisopropyl 2,3-diethyl succinate, diisopropyl 2,3-di-n-propyl succinate, diisopropyl 2,3-diisopropyl succinate, diisopropyl 2,3-di-n-butyl succinate, diisopropyl 2,3-diisobutyl succinate; Di-n-butyl succinate, di-n-butyl 2,3-dimethyl succinate, di-n-butyl 2,3-diethyl succinate, di-n-butyl 2,3-di-n-propyl succinate, di-n-butyl 2,3-diisopropyl succinate, di-n-butyl 2,3-di-n-butyl succinate, di-n-butyl 2,3-diisobutyl succinate; Diisobutyl succinate, diisobutyl 2,3-dimethylsuccinate, diisobutyl 2,3-diethylsuccinate, diisobutyl 2,3-di-n-propylsuccinate, diisobutyl 2,3-diisopropylsuccinate, diisobutyl 2,3-di-n-butylsuccinate, diisobutyl 2,3-diisobutylsuccinate; One or more selected from the following can be mentioned. Among these dialkyl succinate esters, diethyl succinate, di-n-propyl succinate, di-n-butyl succinate, diisobutyl succinate, diethyl 2,3-di-n-propyl succinate, diethyl 2,3-diisopropyl succinate, di-n-propyl 2,3-diisopropyl succinate, diisopropyl 2,3-di-n-propyl succinate, diisopropyl 2,3-diisopropyl succinate, di-n-butyl 2,3-di-n-propyl succinate, di-n-butyl 2,3-diisopropyl succinate, diisobutyl 2,3-di-n-propyl succinate, and diisobutyl 2,3-diisopropyl succinate are preferably used.

[0046] The solid catalyst component for olefin polymerization according to the present invention contains, as internal electron donor compounds, a 1,3-diether compound not having a fluorene structure and a succinic acid diester compound as essential components, but may further contain other internal electron donor compounds (hereinafter, appropriately referred to as "other internal electron donor compounds") as internal electron donor compounds other than the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound.

[0047] Such other internal electron donor compounds include at least one selected from carbonates, acid halides, acid amides, nitriles, acid anhydrides, diether compounds, and carboxylates.

[0048] Specific examples of such other internal electron donor compounds include one or more compounds selected from ether carbonate compounds, carboxylic acid diesters such as cycloalkane dicarboxylic acid diesters, cycloalkene dicarboxylic acid diesters, malonic acid diesters, alkyl-substituted malonic acid diesters, and maleic acid diesters, and diether compounds. More specifically, one or more selected from ether carbonate compounds such as (2-ethoxyethyl)methyl carbonate, (2-ethoxyethyl)ethyl carbonate, and (2-ethoxyethyl)phenyl carbonate, dialkyl malonic acid diesters such as dimethyl diisobutylmalonate and diethyl diisobutylmalonate, and cycloalkane dicarboxylic acid diesters such as dimethyl cyclohexane-1,2-dicarboxylate are more preferable.

[0049] On the other hand, the solid catalyst component for olefin polymerization according to the present invention suitably has a phthalate content of 0.2 mass % or less (0.0 to 0.2 mass %), more suitably 0.1 mass % or less (0.0 to 0.1 mass %), and further suitably 0.0 mass % (substantially containing no phthalate (below the detection limit)).

[0050] In the solid catalyst component for olefin polymerization according to the present invention, the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of the components is 13.0% by mass or more, preferably 14.0% by mass or more, more preferably 15.0% by mass or more, when calculated as solid content. In addition, in the solid catalyst component for olefin polymerization according to the present invention, the upper limit of the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of the components is not particularly limited, but the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of the components is preferably 25.0% by mass or less, more preferably 21.0% by mass or less. When the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of components contained in the total amount of components contained in the solid content conversion is within the above range, an olefin polymer having excellent fluidity and high rigidity can be easily produced when subjected to polymerization of olefins.

[0051] In the solid catalyst component for olefin polymerization according to the present invention, the content of titanium atoms in the total amount of components contained, calculated as solid content, is 2.0 to 6.0 mass%, preferably 2.5 to 5.0 mass%, more preferably 2.5 to 4.0 mass%. When the content of titanium atoms in the total amount of components contained, calculated as solid content, is within the above range, an olefin polymer having excellent fluidity and high rigidity can be easily produced when the catalyst component is subjected to polymerization of olefins.

[0052] In the solid catalyst component for olefin polymerization according to the present invention, the molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound contained in the total amount of components relative to the molar amount (T) of titanium contained in the total amount of components is 0.71 to 1.30, preferably 0.71 to 1.10, and more preferably 0.80 to 1.10. When the molar ratio (S / T) is within the above range, an olefin polymer having excellent fluidity and high rigidity can be easily produced when subjected to polymerization of olefins.

[0053] In the solid catalyst component for olefin polymerization according to the present invention, the molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure in the total amount of the components relative to the molar amount (S) of the succinic acid diester compound in the total amount of the components is 0.10 to 0.70, preferably 0.10 to 0.50, and more preferably 0.10 to 0.40. When the molar ratio (E / S) is within the above range, an olefin polymer having excellent fluidity and high rigidity can be easily produced when subjected to polymerization of olefins.

[0054] The solid catalyst component for olefin polymerization according to the present invention has a total pore volume of 0.3 to 1.0 cm3 having a diameter of 1 μm or less as measured by mercury intrusion porosimetry. 3 / g, preferably 0.3 to 0.8 cm 3 / g, more preferably 0.3 to 0.6 cm 3 When the solid catalyst component for olefin polymerization according to the present invention has a total pore volume of 1 μm or less in diameter measured by mercury intrusion porosimetry within the above range, the rubber component can be sufficiently retained within the particles when subjected to block polymerization of olefins, and a block copolymer having excellent fluidity can be easily produced.

[0055] The solid catalyst component for olefin polymerization according to the present invention has a specific surface area of ​​200 m2 or less as measured by mercury intrusion porosimetry. 2 / g or more, preferably 300 to 500m 2 / g, more preferably 350 to 500m 2When the solid catalyst component for olefin polymerization according to the present invention has a specific surface area measured by mercury intrusion porosimetry within the above range, when the solid catalyst component is subjected to polymerization of olefins, particularly copolymerization of olefins, the olefins enter into pores formed on the surface of the solid catalyst component and are subjected to a polymerization reaction within the pores, so that an olefin polymer can be prepared under high polymerization activity, and the polymerization reaction can be easily carried out under high operability while suppressing stickiness on the surface of the solid catalyst component due to the production of the copolymer.

[0056] The solid catalyst component for olefin polymerization according to the present invention has a total pore volume and specific surface area having a diameter of 1 μm or less measured by mercury intrusion porosimetry within the above-mentioned ranges, and the sum of the content of 1,3-diether compounds not having a fluorene structure and the content of succinic acid diester compounds in the total amount of components, the molar ratio (S / T) represented by the molar amount (S) of succinic acid diester compounds to the molar amount (T) of titanium, and the molar ratio (E / S) represented by the molar amount (E) of 1,3-diether compounds not having a fluorene structure to the molar amount (S) of succinic acid diester compounds are within the above-mentioned predetermined values, whereby the olefin polymer obtained by using the solid catalyst component can have a high rigidity while having a high melt flow rate and can reduce the amount of low molecular weight polymers produced.

[0057] The solid catalyst component for olefin polymerization in the present invention may contain a polysiloxane.

[0058] Since the solid catalyst component for olefin polymerization in the present invention contains a polysiloxane, when olefins are polymerized, the stereoregularity or crystallinity of the resulting polymer can be easily improved, and further, the amount of fine powder in the produced polymer can be easily reduced. Polysiloxane is a polymer having a siloxane bond (-Si-O- bond) in the main chain, and is also called silicone oil. It has a viscosity of 0.02 to 100.00 cm at 25°C. 2 / s (2 to 10,000 centistokes), more preferably 0.03 to 5.00 cm2 / s (3 to 500 centistokes) and is liquid or viscous at room temperature.

[0059] Examples of the linear polysiloxane include dimethylpolysiloxane and methylphenylpolysiloxane. Examples of the partially hydrogenated polysiloxane include methylhydrogenpolysiloxane having a hydrogenation rate of 10 to 80%. Examples of the cyclic polysiloxane include one or more selected from hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, 2,4,6-trimethylcyclotrisiloxane, and 2,4,6,8-tetramethylcyclotetrasiloxane.

[0060] The solid catalyst component for olefin polymerization according to the present invention is preferably prepared by contacting the above-mentioned dialkoxymagnesium, titanium halide compound and succinic acid diester compound in the presence of an inert organic solvent.

[0061] In the present invention, the inert organic solvent is preferably one which dissolves the titanium halide compound but does not dissolve the dialkoxymagnesium, and specific examples thereof include one or more selected from saturated hydrocarbon compounds such as pentane, hexane, heptane, octane, nonane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, 1,2-diethylcyclohexane, methylcyclohexene, decalin, and mineral oil; aromatic hydrocarbon compounds such as benzene, toluene, xylene, and ethylbenzene; and halogenated hydrocarbon compounds such as ortho-dichlorobenzene, methylene chloride, 1,2-dichlorobenzene, carbon tetrachloride, and dichloroethane. As the inert organic solvent, a saturated hydrocarbon compound or an aromatic hydrocarbon compound having a boiling point of about 50 to 200° C. and being liquid at room temperature is preferably used. Among them, one or more selected from hexane, heptane, octane, ethylcyclohexane, mineral oil, toluene, xylene, and ethylbenzene are preferred, and one or more selected from hexane, heptane, ethylcyclohexane, and toluene are particularly preferred.

[0062] In the solid catalyst component for olefin polymerization according to the present invention, magnesium, titanium, halogen, a 1,3-diether compound not having a fluorene structure, and a succinic acid diester compound can each be contained in a desired amount, so long as the total content of the above-mentioned 1,3-diether compound not having a fluorene structure and the above-mentioned succinic acid diester compound, the molar ratio represented by the content (molar amount) of the above-mentioned succinic acid diester compound / the content (molar amount) of titanium, and the molar ratio represented by the 1,3-diether compound not having a fluorene structure (molar amount) / the succinic acid diester compound satisfy the above-mentioned regulations.

[0063] The solid catalyst component for olefin polymerization according to the present invention preferably contains titanium in an amount of 3.0 to 6.0 mass %, more preferably 3.5 to 6.0 mass %, and even more preferably 4.0 to 6.0 mass %, calculated as atomic weight. The solid catalyst component for olefin polymerization according to the present invention contains, in atomic weight conversion, preferably 15.0 to 25.0 mass %, more preferably 16.0 to 23.0 mass %, further preferably 17.0 to 22.0 mass %, and even more preferably 18.0 to 21.0 mass % of magnesium. The solid catalyst component for olefin polymerization according to the present invention contains, in atomic weight conversion, preferably 50.0 to 70.0 mass %, more preferably 55.0 to 68.0 mass %, further preferably 58.0 to 67.0 mass %, and even more preferably 60.0 to 66.0 mass % of halogen.

[0064] In the present application, the titanium content in the solid catalyst component for olefin polymerization means a value measured in accordance with the method (oxidation-reduction titration) described in JIS 8311-1997 "Method for determining titanium in titanium ore."

[0065] In the present application, the content of magnesium in the solid catalyst component for olefin polymerization means a value measured by an EDTA titration method in which the solid catalyst component for olefin polymerization is dissolved in a hydrochloric acid solution and titrated with an EDTA solution.

[0066] In the present application, the content of halogen contained in the solid catalyst component for olefin polymerization means a value measured by a silver nitrate titration method in which the solid catalyst component is treated with a mixed solution of sulfuric acid and pure water to prepare an aqueous solution, a predetermined amount of which is then separated and the halogen is titrated with a standard silver nitrate solution.

[0067] Furthermore, in the present application, the contents of 1,3-diether compounds not having a fluorene structure, succinic acid diester compounds and other internal electron donor compounds added as required contained in the solid catalyst component for olefin polymerization refer to values ​​obtained by hydrolyzing the solid catalyst component for olefin polymerization, extracting the 1,3-diether compounds not having a fluorene structure, succinic acid diester compounds and other internal electron donor compounds added as required with an aromatic solvent, and measuring the solution by gas chromatography FID (Flame Ionization Detector).

[0068] The solid catalyst component for olefin polymerization according to the present invention can be suitably produced by the method for producing a solid catalyst component for olefin polymerization according to the present invention described below.

[0069] Next, the method for producing the solid catalyst component for olefin polymerization according to the present invention will be described. The method for producing a solid catalyst component for olefin polymerization according to the present invention comprises the steps of: A method for producing a solid catalyst component for olefin polymerization by contacting a dialkoxymagnesium, a titanium halogen compound, a 1,3-diether compound not having a fluorene structure, and a succinic acid diester compound with each other, comprising the steps of: contacting the dialkoxymagnesium with the titanium halide compound multiple times; When the dialkoxymagnesium is initially contacted with the titanium halide compound, the amount of the titanium halide compound contacted is 1.5 to 10.0 mol per 1.0 mol of the dialkoxymagnesium, the total amount of the titanium halide compound used is 5.0 to 18.0 mol per 1.0 mol of the dialkoxymagnesium; the total molar amount of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound is 0.10 to 0.20 mol per 1.0 mol of the dialkoxymagnesium, a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound to the total molar amount (T) of the titanium halide compound is 0.020 to 0.040; a molar ratio (E / S) of the succinic acid diester compound to the 1,3-diether compound not having a fluorene structure (E) being 0.50 or less; The dialkoxymagnesium is composed of secondary particles that are aggregates of primary particles having an average particle diameter of less than 2 μm, and has a specific surface area of ​​10 m 2 / g or more 50m 2 / g and the particle size distribution index (SPAN) is 1.30 or less. The present invention is characterized by the following:

[0070] The dialkoxymagnesium used in the method for producing a solid catalyst component for olefin polymerization according to the present invention is the same as the dialkoxymagnesium described above for the solid catalyst component for olefin polymerization according to the present invention.

[0071] The dialkoxymagnesium used in the method for producing a solid catalyst component for olefin polymerization according to the present invention is composed of secondary particles that are aggregates of primary particles having an average particle diameter of less than 2 μm. The dialkoxymagnesium used in the method for producing a solid catalyst component for olefin polymerization according to the present invention has a specific surface area of ​​10 m 2 / g or more 50m 2 / g or less, 10-50m 2 / g is more preferable, and 10 to 40m 2 The dialkoxymagnesium used in the method for producing a solid catalyst component for olefin polymerization according to the present invention has a particle size distribution index (SPAN) of 1.30 or less, preferably 0.60 to 1.00, and more preferably 0.70 to 0.90.

[0072] The 1,3-diether compound and succinic acid diester compound not having a fluorene structure used in the production method of the solid catalyst component for olefin polymerization according to the present invention are the same as the 1,3-diether compound and succinic acid diester compound not having a fluorene structure described above in the solid catalyst component for olefin polymerization according to the present invention.

[0073] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, the dialkoxymagnesium is contacted with a titanium halide compound multiple times, and when the dialkoxymagnesium is initially contacted with the titanium halide compound, 1.5 to 10.0 mol of the titanium halide compound is used per 1.0 mol of the dialkoxymagnesium, preferably 2.0 to 8.0 mol, and a total amount of 5.0 to 18.0 mol of the titanium halide compound is used per 1.0 mol of the dialkoxymagnesium, preferably 5.0 to 15.0 mol of the titanium halide compound is used per 1.0 mol of the dialkoxymagnesium, and a total amount of 5.0 to 12.0 mol of the titanium halide compound is used per 1.0 mol of the dialkoxymagnesium.

[0074] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, when the dialkoxymagnesium is first contacted with a titanium halide compound, the amount of the titanium halide compound used relative to the dialkoxymagnesium is controlled within the above range, thereby making it possible to prepare a solid catalyst component for olefin polymerization that exhibits high activity with a small amount of the titanium halide compound.

[0075] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, by controlling the total amount of titanium compounds used per 1.0 mole of dialkoxymagnesium within the above range, a solid catalyst component for olefin polymerization that exhibits high activity with a small amount of titanium halide compounds can be prepared.

[0076] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, the amount of the succinic acid diester compound per 1.0 mol of dialkoxymagnesium is preferably 0.08 to 0.16 mol, more preferably 0.09 to 0.15 mol, and even more preferably 0.10 to 0.14 mol of the succinic acid diester compound per 1.0 mol of dialkoxymagnesium.

[0077] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, by controlling the amount of the succinic acid diester compound used per 1.0 mole of dialkoxymagnesium within the above range, it is possible to sufficiently support the succinic acid diester compound while suppressing excessive support of the titanium halide compound on the support.

[0078] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, it is preferable that the total molar amount of the 1,3-diether compound not having a fluorene structure and the molar amount of the succinic acid diester compound used is 0.10 to 0.20 mol per 1.0 mol of dialkoxymagnesium, and the total molar amount of the 1,3-diether compound not having a fluorene structure and the molar amount of the succinic acid diester compound used is 0.12 to 0.18 mol per 1.0 mol of dialkoxymagnesium.

[0079] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, by controlling the total molar amount of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound to be used relative to 1.0 mole of dialkoxymagnesium within the above-mentioned range, it is possible to sufficiently support the 1,3-diether compound and the succinic acid diester compound while suppressing excessive support of the titanium halide compound on the support.

[0080] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, the molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound to the total molar amount (T) of the titanium halide compounds is 0.020 to 0.040, preferably 0.022 to 0.030, and more preferably 0.024 to 0.030.

[0081] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, by controlling the molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound to the total molar amount (T) of the titanium halide compounds to be used within the above-mentioned range, it is possible to suppress excessive support of the titanium halide compounds on the support while ensuring sufficient support of the 1,3-diether compound and the succinic acid diester compound.

[0082] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, the molar ratio (E / S) represented by the molar amount (E) of a 1,3-diether compound not having a fluorene structure to the molar amount (S) of a succinic acid diester compound is 0.50 or less, preferably 0.10 to 0.40, and more preferably 0.20 to 0.40.

[0083] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, by controlling the molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure to the molar amount (S) of the succinic acid diester compound used within the above-mentioned range, it is possible to sufficiently support the 1,3-diether compound and the succinic acid diester compound while suppressing excessive support of the titanium halide compound on the support.

[0084] More specifically, the method for producing the solid catalyst component for olefin polymerization according to the present invention may include a method in which a dialkoxymagnesium, a titanium halide compound, a 1,3-diether compound not having a fluorene structure, and a succinic acid diester compound are suspended in an inert hydrocarbon solvent and contacted with each other for a predetermined period of time while heating, a titanium halide compound is further added to the suspension obtained, and the suspension is contacted with the compounds while heating to obtain a solid product, and the solid product is washed with a hydrocarbon solvent to obtain the desired solid catalyst component for olefin polymerization.

[0085] The inert organic solvent is preferably a liquid at room temperature (20°C) and has a boiling point of 50 to 150°C, and more preferably an aromatic hydrocarbon compound or a saturated hydrocarbon compound that is a liquid at room temperature and has a boiling point of 50 to 150°C.

[0086] Specific examples of the inert organic solvent include one or more selected from linear aliphatic hydrocarbon compounds such as hexane, heptane, and decane; branched aliphatic hydrocarbon compounds such as methylheptane; alicyclic hydrocarbon compounds such as cyclohexane, methylcyclohexane, and ethylcyclohexane; and aromatic hydrocarbon compounds such as toluene, xylene, and ethylbenzene. Among the above inert organic solvents, aromatic hydrocarbon compounds that are liquid at room temperature and have a boiling point of 50 to 150°C are preferred because they can improve the activity of the resulting solid catalyst component and the stereoregularity of the resulting polymer.

[0087] The heating temperature is preferably from 70 to 150°C, more preferably from 80 to 120°C, and further preferably from 90 to 115°C. The heating time is preferably from 30 to 240 minutes, more preferably from 60 to 180 minutes, and even more preferably from 60 to 120 minutes.

[0088] The number of times the titanium halide compound is added to the suspension is not particularly limited. When the titanium halide compound is added to the suspension a plurality of times, the heating temperature for each addition should be within the above range, and the heating time for each addition should be within the above range.

[0089] In the method for producing a solid catalyst component for olefin polymerization of the present invention, the timing for contacting the dialkoxymagnesium with the succinic acid diester compound may be before the dialkoxymagnesium is contacted with a titanium halogen compound for the first time, after the dialkoxymagnesium is contacted with a titanium halogen compound for the first time, before or after contacting the titanium halogen compound multiple times, before washing the solid product with a hydrocarbon solvent, etc. In the method for producing a solid catalyst component for olefin polymerization of the present invention, the timing for contacting the dialkoxymagnesium with the succinic acid diester compound is preferably after the dialkoxymagnesium is contacted with a titanium halogen compound for the first time, in that the succinic acid diester compound can be sufficiently supported while suppressing particle aggregation between the carriers.

[0090] In the method for producing a solid catalyst component for olefin polymerization of the present invention, the timing for contacting a 1,3-diether compound not having a fluorene structure with a dialkoxymagnesium may be before contacting a titanium halide compound with a dialkoxymagnesium for the first time, after contacting a titanium halide compound with a dialkoxymagnesium for the first time, before or after contacting a titanium halide compound multiple times, before washing a solid product with a hydrocarbon solvent, etc. In the method for producing a solid catalyst component for olefin polymerization of the present invention, the timing for contacting a 1,3-diether compound not having a fluorene structure with a dialkoxymagnesium is preferably after contacting a titanium halide compound with a dialkoxymagnesium for the first time, in that it can suppress particle aggregation between carriers and sufficiently support the 1,3-diether compound.

[0091] In addition, in the method for producing a solid catalyst component for olefin polymerization of the present invention, a 1,3-diether compound not having a fluorene structure may be contacted with a dialkoxy magnesium together with a succinic acid diester compound, or a dialkoxy magnesium may be contacted with a succinic acid diester compound first, and then with a 1,3-diether compound not having a fluorene structure. In the method for producing a solid catalyst component for olefin polymerization of the present invention, it is preferable to contact a dialkoxy magnesium with a succinic acid diester compound first, and then with a 1,3-diether compound not having a fluorene structure, since it is possible to sufficiently support a succinic acid diester compound while suppressing excessive support of 1,3-diether on the support.

[0092] In the above preparation method, in addition to the succinic acid diester compound, other internal electron donor compounds may be used in combination. Furthermore, the contact may be carried out in the presence of other reaction agents such as silicon, phosphorus, aluminum, etc., or a surfactant.

[0093] In the method for producing a solid catalyst component for olefin polymerization according to the present invention, suitable embodiments of the obtained solid catalyst component for olefin polymerization are as described above in the description of the solid catalyst component for olefin polymerization according to the present invention.

[0094] Next, the olefin polymerization catalyst according to the present invention will be described. The olefin polymerization catalyst according to the present invention comprises (I) The solid catalyst component for olefin polymerization according to the present invention, and (II) the following general formula (3); R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is 0. <p≦3であり、R 9 If there are multiple R 5 may be the same or different, and when there are multiple Qs, each Q may be the same or different. The present invention is characterized in that it contains an organoaluminum compound represented by the following formula: The olefin polymerization catalyst according to the present invention includes (I) The solid catalyst component for olefin polymerization according to the present invention, (II) the following general formula (3); R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is 0 <p≦3であって、R 9 If there are multiple R 5 may be the same or different, and when there are a plurality of Q's, each Q may be the same or different. (III) External electron donor compound It is preferable that the composition contains the following:

[0095] The details of the solid catalyst component for olefin polymerization according to the present invention, which constitutes the catalyst for olefin polymerization according to the present invention, are as described above.

[0096] In the catalyst for olefin polymerization according to the present invention, (II) the organoaluminum compound is represented by the following general formula (3); R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p is 0 < p ≦ 3, and when a plurality of R 9 are present, each R 5 may be the same as or different from each other, and when a plurality of Q are present, each Q may be the same as or different from each other.) It is represented by.

[0097] In the compound represented by the general formula (3), p is 0 < p ≦ 3, and specifically, examples of p include 1, 2, or 3.

[0098] Specific examples of such (II) organoaluminum compounds include one or more selected from trialkylaluminums such as triethylaluminum, triisopropylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, triisobutylaluminum, alkylaluminum halides such as diethylaluminum chloride, diethylaluminum bromide, and diethylaluminum hydride. One or more selected from alkylaluminum halides such as diethylaluminum chloride, trialkylaluminums such as triethylaluminum, tri-n-butylaluminum, and triisobutylaluminum are preferred, and one or more selected from triethylaluminum and triisobutylaluminum are more preferred.

[0099] As the (III) external electron donor compound constituting the catalyst for olefin polymerization of the present invention, For example, the following general formula (5) R 11 r Si(NR 12 R 13 ) s (OR 14 ) 4-(r+s) (5) (In the formula, r is 0 or 1 to 2, s is 0 or 1 to 2, r+s is 0 or 1 to 4, R 11 , R 12 or R 13 R is a hydrogen atom or a group selected from a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, which may contain a heteroatom and may be the same or different from each other. 12 or R 13 may be linked to form a ring, R 11 , R 12 and R 13 may be the same or different. 14 is any group selected from an alkyl group, a cycloalkyl group, a phenyl group, a vinyl group, an allyl group and an aralkyl group having 1 to 4 carbon atoms, and may contain a heteroatom.

[0100] In the compound represented by the above general formula (5), R 11 represents a hydrogen atom or a group selected from a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, which may contain a heteroatom. R 11 As the alkyl group, a linear or branched alkyl group having 1 to 10 carbon atoms or a cycloalkyl group having 5 to 8 carbon atoms is preferable, and a linear or branched alkyl group having 1 to 8 carbon atoms or a cycloalkyl group having 5 to 8 carbon atoms is particularly preferable.

[0101] In the compound represented by the above general formula (5), R 12 or R 13represents a hydrogen atom or a group selected from a linear or branched alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group, which may contain a heteroatom. R 12 or R 13 As the alkyl group, a linear or branched alkyl group having 1 to 10 carbon atoms and a cycloalkyl group having 5 to 8 carbon atoms are preferable, and a linear or branched alkyl group having 1 to 8 carbon atoms and a cycloalkyl group having 5 to 8 carbon atoms are particularly preferable. Also, R 12 or R 13 may be bonded to form a ring shape, in which case (NR 12 or R 13 ) is preferably a perhydroquinolino group or a perhydroisoquinolino group.

[0102] In the compound represented by the above general formula (5), R 11 , R 12 and R 13 may be the same or different.

[0103] In the compound represented by the above general formula (5), R 14 is any group selected from an alkyl group, a cycloalkyl group, a phenyl group, an allyl group, and an aralkyl group having 1 to 4 carbon atoms, and may contain a heteroatom. R 14 As the alkyl group, a linear or branched alkyl group having 1 to 4 carbon atoms is preferable.

[0104] In the compound represented by the above general formula (5), r is 0 or 1 to 2, and specifically, r is 0, 1 or 2. In the compound represented by the above general formula (5), s is 0 or 1 to 2, and specifically, s is 0, 1 or 2. In the compound represented by the above general formula (5), r+s is 0 or 1 to 4, and specifically, r+s is 0, 1, 2, 3, or 4.

[0105] Specific examples of such compounds represented by the above general formula (5) include one or more organosilicon compounds selected from phenylalkoxysilanes, alkylalkoxysilanes, phenylalkylalkoxysilanes, cycloalkylalkoxysilanes, cycloalkylalkylalkoxysilanes, (alkylamino)alkoxysilanes, alkyl(alkylamino)alkoxysilanes, alkyl(alkylamino)silanes, alkylaminosilanes, and the like.

[0106] Particularly preferred compounds in which s is 0 in the above general formula (5) include di-n-propyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, di-t-butyldimethoxysilane, t-butylmethyldimethoxysilane, t-butylethyldimethoxysilane, di-n-butyldiethoxysilane, t-butyltrimethoxysilane, t-butyltriethoxysilane, dicyclohexyldimethoxysilane, dicyclohexyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylethyldimethylsilane, and cyclohexylethyldimethylsilane.

[0043] Examples of the organic silicon compound include one or more organic silicon compounds selected from the group consisting of cyclohexylsilane, cyclohexyl ethyl diethoxysilane, dicyclopentyl dimethoxysilane, dicyclopentyl diethoxysilane, cyclopentyl methyl dimethoxysilane, cyclopentyl methyl diethoxysilane, cyclopentyl ethyl diethoxysilane, cyclohexyl cyclopentyl dimethoxysilane, cyclohexyl cyclopentyl diethoxysilane, 3-methylcyclohexyl cyclopentyl dimethoxysilane, 4-methylcyclohexyl cyclopentyl dimethoxysilane, and 3,5-dimethylcyclohexyl cyclopentyl dimethoxysilane.

[0107] Examples of the compound in which s in the above general formula (5) is 1 or 2 include one or more organosilicon compounds selected from di(alkylamino)dialkoxysilanes, (alkylamino)(cycloalkylamino)dialkoxysilanes, (alkylamino)(alkyl)dialkoxysilanes, di(cycloalkylamino)dialkoxysilanes, vinyl(alkylamino)dialkoxysilanes, allyl(alkylamino)dialkoxysilanes, (alkoxyamino)trialkoxysilanes, (alkylamino)trialkoxysilanes, (cycloalkylamino)trialkoxysilanes, and the like. Particularly preferred are ethyl(t-butyl)amino Examples of the organic silicon compound include bis(perhydroisoquinolino)dimethoxysilane, cyclohexyl(cyclohexylamino)dimethoxysilane, ethyl(t-butylamino)dimethoxysilane, bis(cyclohexylamino)dimethoxysilane, bis(perhydroisoquinolino)dimethoxysilane, bis(perhydroquinolino)dimethoxysilane, ethyl(isoquinolino)dimethoxysilane, diethylaminotrimethoxysilane, and diethylaminotriethoxysilane. Among these, there are at least one organic silicon compound selected from bis(perhydroisoquinolino)dimethoxysilane, diethylaminotrimethoxysilane, and diethylaminotriethoxysilane.

[0108] The compounds represented by the above general formula (5) may be used in combination of two or more kinds.

[0109] The catalyst for olefin polymerization according to the present invention is a catalyst containing (I) the solid catalyst component for olefin polymerization according to the present invention and (II) an organoaluminum compound represented by general formula (3), or a catalyst containing (I) the solid catalyst component for olefin polymerization according to the present invention, (II) an organoaluminum compound represented by general formula (3), and (III) an external electron-donor compound, i.e., a contact product thereof. The catalyst for olefin polymerization according to the present invention may be prepared by contacting (I) the solid catalyst component for olefin polymerization according to the present invention with (II) an organoaluminum compound represented by general formula (3), or further with (III) an external electron donor compound, in the absence of olefins, or may be prepared by contacting them in the presence of olefins (in the polymerization system) as described below.

[0110] In the olefin polymerization catalyst according to the present invention, the content ratio of each component is arbitrary as long as it does not affect the effects of the present invention, and is not particularly limited, but usually, per 1 mole of titanium atom in the (I) solid catalyst component for olefin polymerization, the (II) organoaluminum compound is preferably contained in an amount of 1 to 2000 moles, more preferably 50 to 1000 moles. Also, per 1 mole of the (II) organoaluminum compound, the olefin polymerization catalyst according to the present invention preferably contains 0.002 to 10.000 moles, more preferably 0.010 to 2.000 moles, and even more preferably 0.010 to 0.500 moles of the (III) external electron donor compound.

[0111] According to the present invention, there can be provided a catalyst for olefin polymerization that contains an internal electron donor compound other than a phthalate ester and can easily produce an olefin polymer having excellent melt flowability and high rigidity. In addition, according to the present invention, there can be provided a solid catalyst for olefin polymerization that can improve catalyst particles and copolymerization performance in addition to achieving both the above-mentioned excellent melt flowability and high rigidity.

[0112] Next, the process for producing an olefin polymer according to the present invention will be described. The process for producing an olefin polymer according to the present invention is characterized in that olefins are polymerized in the presence of the olefin polymerization catalyst according to the present invention.

[0113] In the process for producing an olefin polymer according to the present invention, the polymerization of olefins may be homopolymerization or copolymerization. In the method for producing an olefin polymer according to the present invention, the olefin to be polymerized may be one or more selected from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane, etc., and among these, one or more selected from ethylene, propylene, and 1-butene are preferred, and propylene is more preferred. When the olefin is propylene, it may be a homopolymer of propylene or a copolymer of propylene with other α-olefins. The olefins to be copolymerized with propylene include one or more selected from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane, and the like.

[0114] When the catalyst for olefin polymerization according to the present invention is prepared in the presence of olefins (within the polymerization system), the ratio of the amounts of each component used is arbitrary as long as it does not affect the effects of the present invention, and is not particularly limited, but usually, the above-mentioned (II) organoaluminum compound is preferably contacted in an amount of 1 to 2000 moles, more preferably 50 to 1000 moles, per mole of titanium atom in the above-mentioned (I) solid catalyst component for olefin polymerization. Also, the above-mentioned (III) external electron donor compound is preferably contacted in an amount of 0.002 to 10.000 moles, more preferably 0.010 to 2.000 moles, and even more preferably 0.010 to 0.500 moles, per mole of the above-mentioned (II) organoaluminum compound.

[0115] The order of contacting the components constituting the above-mentioned olefin polymerization catalyst may be arbitrary, but it is preferable to first charge the above-mentioned (II) organoaluminum compound into the polymerization system, and then, when the above-mentioned (III) external electron donor compound is used, charge the above-mentioned (III) external electron donor compound and contact it, and then charge and contact the above-mentioned (I) solid catalyst component for olefin polymerization.

[0116] The process for producing an olefin polymer according to the present invention may be carried out in the presence or absence of an organic solvent. In addition, olefin monomers such as propylene can be used in either a gaseous or liquid state. The polymerization temperature is preferably 200°C or less, more preferably 100°C or less, and the polymerization pressure is preferably 10 MPa or less, more preferably 5 MPa or less. In addition, the polymerization of olefins can be performed by either a continuous polymerization method or a batch polymerization method. Furthermore, the polymerization reaction may be performed in one stage or in two or more stages.

[0117] In addition, when polymerizing olefins using the olefin polymerization catalyst according to the present invention (also referred to as main polymerization), in order to further improve the catalytic activity, stereoregularity, particle properties of the produced polymer, etc., it is preferable to carry out prepolymerization prior to the main polymerization, and in the prepolymerization, the same olefins or monomers such as styrene as those used in the main polymerization can be used.

[0118] In carrying out the prepolymerization, the order of contacting each component constituting the above-mentioned catalyst for olefin polymerization with the monomer (olefin) is arbitrary, but it is preferable to first charge (II) an organoaluminum compound into a prepolymerization system set in an inert gas atmosphere or an olefin gas atmosphere, then charge (I) the solid catalyst component for olefin polymerization according to the present invention, and after contacting them, contact them with an olefin such as propylene alone or a mixture of an olefin such as propylene and one or more other olefins. In the above prepolymerization, when an external electron-donor compound (III) is further charged into the prepolymerization system, it is preferred that the organoaluminum compound (II) is first charged into the prepolymerization system set in an inert gas atmosphere or an olefin gas atmosphere, and then the external electron-donor compound (III) is charged and contacted with the solid catalyst component for olefin polymerization according to the present invention (I), and then the solid catalyst component is contacted with an olefin such as propylene alone or a mixture of an olefin such as propylene and one or more other olefins.

[0119] In the method for producing an olefin polymer according to the present invention, examples of the polymerization method include a slurry polymerization method using a solvent of an inert hydrocarbon compound such as cyclohexane or heptane, a bulk polymerization method using a solvent such as liquefied propylene, and a gas phase polymerization method which does not substantially use a solvent, and the bulk polymerization method or the gas phase polymerization method is preferred.

[0120] When copolymerizing propylene with other α-olefin monomers, representative methods include random copolymerization in which propylene and a small amount of ethylene are polymerized in one stage as comonomers, and so-called propylene-ethylene block copolymerization in which propylene is homopolymerized in the first stage (first polymerization tank) and then copolymerized with propylene and other α-olefins such as ethylene in the second stage (second polymerization tank) or multiple stages (multistage polymerization tank). Block copolymerization of propylene with other α-olefins is preferred.

[0121] A block copolymer obtained by block copolymerization is a polymer containing segments in which two or more types of monomer composition change continuously, and refers to a form in which two or more types of polymer chains (segments) with different primary structures of the polymer, such as monomer type, comonomer type, comonomer composition, comonomer content, comonomer sequence, and stereoregularity, are linked in a single molecular chain.

[0122] In the method for producing an olefin polymer according to the present invention, the block copolymerization reaction of propylene with other α-olefins can usually be carried out in the presence of the olefin polymerization catalyst according to the present invention by contacting propylene alone or propylene with a small amount of α-olefin (ethylene, etc.) in the first stage, and then contacting propylene with α-olefin (ethylene, etc.) in the second stage. The polymerization reaction in the first stage may be repeated multiple times, or the polymerization reaction in the second stage may be repeated multiple times to carry out a multi-stage reaction.

[0123] Specifically, the block copolymerization reaction of propylene with other α-olefins is preferably carried out in a first step by adjusting the polymerization temperature and time so that the proportion of the polypropylene part (in the final copolymer) is 20 to 90% by mass, and then in a second step by introducing propylene and ethylene or other α-olefins, polymerization is preferably carried out so that the proportion of the rubber part, such as ethylene-propylene rubber (EPR), is 10 to 80% by mass (in the final copolymer). The polymerization temperature in both the first and second stages is preferably 200° C. or less, more preferably 100° C. or less, even more preferably 65 to 80° C., and still more preferably 75 to 80° C., and the polymerization pressure is preferably 10 MPa or less, more preferably 6 MPa or less, and even more preferably 5 MPa or less. In the copolymerization reaction, either a continuous polymerization method or a batch polymerization method can be used, and the polymerization reaction may be carried out in one stage or in two or more stages. The polymerization time (residence time in the reactor) is preferably 1 minute to 5 hours in each polymerization stage of the previous or subsequent polymerization stages, or in the case of continuous polymerization. Examples of the polymerization method include a slurry polymerization method using a solvent of an inert hydrocarbon compound such as cyclohexane or heptane, a bulk polymerization method using a solvent such as liquefied propylene, and a gas phase polymerization method which does not substantially use a solvent, and the bulk polymerization method or the gas phase polymerization method is preferred.

[0124] In particular, ethylene-propylene block copolymers contain EPR components (copolymer components of ethylene and propylene), and when the EPR components seep out onto the surface of polymer particles, the particles become sticky (adhesive) and their fluidity deteriorates. Since the deterioration of particle fluidity in polymer production facilities reduces the operability of the plant, it is desirable to select a polymer production method that can suppress the seepage of EPR components onto the particle surface.

[0125] According to the present invention, there is provided a method for easily producing an olefin polymer having excellent melt flowability and high rigidity.

[0126] Next, the olefin polymer according to the present invention will be described. The olefin polymer according to the present invention is (a) a melt flow rate of 0.5 to 200 g / 10 min; (b) A flexural modulus of 1900 MPa or more; (c) the molecular weight distribution is Mw / Mn≧6.0, Mz / Mw≧4.0; It is characterized by the above.

[0127] In the olefin polymer according to the present invention, the melt flow rate (MFR), which indicates the melt flowability of the olefin polymer, is from 0.5 to 200 g / 10 minutes, and preferably from 10 to 160 g / 10 minutes.

[0128] In the olefin polymer according to the present invention, when the melt flow rate (MFR) is within the above range, practically sufficient moldability can be easily exhibited.

[0129] In the present application, the melt flow rate (MFR) refers to a value measured based on ASTM D 1238 and JIS K 7210.

[0130] The olefin polymer according to the present invention has a flexural modulus (FM) of 1900 MPa or more, preferably 2000 to 2300 MPa, and more preferably 2000 to 2200 MPa.

[0131] In the olefin polymer according to the present invention, when the flexural modulus (FM) is within the above range, it has excellent moldability and can exhibit high rigidity.

[0132] In the present application, the flexural modulus (FM) of an olefin polymer refers to a value (unit: MPa) measured at an ambient temperature of 23°C according to JIS K7171 using an injection-molded test piece having a thickness of 4.0 mm, a width of 10.0 mm and a length of 80.0 mm, which was prepared using NEX30III3EG manufactured by Nissei Plastic Industrial Co., Ltd. under conditions of a molding temperature of 200°C and a mold temperature of 40°C.

[0133] Since the olefin polymer according to the present invention satisfies the above-mentioned requirements for melt flow rate and flexural modulus, it has sufficient fluidity for practical use, and therefore has excellent moldability and can easily exhibit excellent rigidity.

[0134] The olefin polymer according to the present invention has a xylene soluble content (c-XS) of 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less.

[0135] In the olefin polymer according to the present invention, the xylene solubles (c-XS) are within the above range, so that the amount of low molecular weight polymers is reduced, and therefore, polypropylene having both high melt flowability and high rigidity can be produced without the low molecular weight polymers adversely affecting the physical properties and moldability of the polymer.

[0136] In this application, the xylene soluble content (c-XS) of the olefin polymer is a value measured by the following procedure. 4.0 g of the polymer (polypropylene) and 200 mL of p-xylene are charged into a flask equipped with a stirrer. The external temperature is raised to the boiling point of xylene (about 150°C), and the polymer is dissolved over 2 hours while maintaining the p-xylene in the flask at a temperature under the boiling point condition (137 to 138°C). The solution is cooled to 23°C over 1 hour, and the insoluble and soluble components are separated by filtration. The solution of the soluble components is collected and heated (dried) under reduced pressure to evaporate the p-xylene. The weight of the residue is calculated, and the relative ratio (mass%) to the polymer (polypropylene) is calculated to determine the xylene soluble content (XS).

[0137] The olefin polymer according to the present invention has a molecular weight distribution (Mw / Mn) of 6.0 or more, preferably from 6.5 to 15.0, and more preferably from 7.0 to 10.0. Furthermore, the olefin polymer according to the present invention has a molecular weight distribution represented by Mz / Mw, which is the ratio of the Z-average molecular weight Mz to the mass-average molecular weight Mw, of 4.0 or more, preferably 4.0 to 8.0, and more preferably 4.5 to 6.0.

[0138] In the olefin polymer according to the present invention, the molecular weight distributions Mw / Mn and Mz / Mw are within the above ranges, so that the olefin polymer contains a large amount of polymers having very high molecular weights and has excellent rigidity.

[0139] In the present application, the molecular weight of the olefin polymer is a value calculated in terms of styrene as measured by gel permeation chromatography (GPC).

[0140] When the olefin polymer according to the present invention is molded into an injection-molded plate, the proportion of the oriented layer in the cross section of the injection-molded plate is preferably 20% or more, more preferably 20 to 50%, and even more preferably 25 to 40%.

[0141] When the olefin polymer of the present invention is molded into an injection-molded plate, the proportion of the oriented layer in the cross section of the injection-molded plate satisfies the above-mentioned specification, so that the thickness of the oriented layer becomes thick, and it is easy to provide a plate with excellent bending elastic modulus.

[0142] In the present application, the proportion of an oriented layer in a cross section of an injection-molded plate of an olefin polymer means a value measured by the following method. 1. Formation of molded products According to JIS K 7152-1 and JIS K 6921-2, an olefin polymer is injection molded under the following conditions to obtain a molded article having the external shape shown in FIG. Equipment: NEX-III-3EG manufactured by Nissei Plastics Co., Ltd. Type of test piece: Multipurpose test piece type A1 as specified in JIS K 7139 Resin melting temperature: 200℃ Mold temperature: 40℃ Injection speed: 180mm / sec Holding pressure: 50MPa - 40 seconds 2. Preparation of measurement samples (thin sections for polarizing microscope observation) (1) As shown in FIG. 1, the obtained molded product is cut in a direction perpendicular to the resin traveling direction MD at a position c1 about 2 cm long from the gate G in the resin traveling direction MD to obtain a cut product S1 shown in FIG. 2(a). (2) As shown in FIG. 2(a), the cut product S1 obtained in (1) is cut in the center (position c2) parallel to the resin traveling direction MD to obtain a cut product S2 shown in FIG. 2(b). (3) As shown in FIG. 2(b), using a rotary microtome device (RX-860 manufactured by Yamato Kogyo Co., Ltd.), the cut piece S2 is cut out at position c3 parallel to the resin traveling direction MD to a thickness of 30 μm to obtain a thin-section measurement sample S3 shown in FIG. 2(c). (4) Figure 2(d) is a schematic diagram showing the obtained flake-shaped measurement sample S3, in which the left side of Figure 2(d) is a side view of the thin flake-shaped measurement sample S3 corresponding to Figure 2(c), and the right side of Figure 2(d) is a front view of the thin flake-shaped measurement sample S4. 3. Polarizing Microscope Observation FIG. 3 is an enlarged front view of the thin-film measurement sample S3 shown on the right side of FIG. 2(d). The above measurement sample S3 is observed with a polarizing microscope (EPCLIPSE LV-100NDA manufactured by NIKON CORPORATION) to identify the core layer c and the orientation layers h1 and h2. The thickness of the core layer is Tc, the thickness of the orientation layers is Th1 and Th2, and the ratio F (%) of the orientation layer to the thickness of the molded layer is calculated using the following formula (6). F(%)=((Th1+Th2) / (Th1+Tc+Th2))×100 (6) The thickness Tc of the core layer and the thicknesses Th1 and Th2 of the alignment layers are calculated by arithmetic average values ​​obtained by measuring the thickness of the core layer c and the thicknesses of the alignment layers h1 and h2 at any 10 points.

[0143] In the case where the olefin polymer according to the present invention is a crystalline polymer, when the molten polymer is poured into a mold for injection molding, the polymer flows into the mold under high shear stress and is cooled, so that oriented crystallization occurs near the surface of the resulting injection molded product. When this injection molded product is thinly sliced ​​with a microtome or the like and the cross section is observed under a polarizing microscope, it is possible to confirm that the oriented layer with high birefringence formed near the surface and the core layer inside are clearly separated, and therefore the thickness Tc of the core layer and the thicknesses Th1 and Th2 of the oriented layers can be easily specified.

[0144] When the olefin polymer of the present invention is measured by cross-fractionation chromatography at a measurement temperature of 40 to 140°C, the ratio of the total amount of olefin polymers eluted at a measurement temperature of 120°C or higher to the total amount of the olefin polymers to be measured is preferably 10% by mass or higher, more preferably 20% by mass or higher, and the content of olefin polymers having a molecular weight of 1,000,000 or higher in the total amount of olefin polymers eluted at a measurement temperature of 120°C or higher is preferably 2% by mass or higher, more preferably 3% by mass or higher.

[0145] The olefin polymer according to the present invention can be easily produced by the process for producing an olefin polymer according to the present invention.

[0146] According to the present invention, it is possible to provide an olefin polymer which has excellent melt flowability and high rigidity and contains a small amount of low molecular weight polymers. EXAMPLES

[0147] Next, the present invention will be described in more detail with reference to examples, but these are merely illustrative and do not limit the present invention.

[0148] Example 1 1. Synthesis of solid catalyst components As the internal electron donor compound, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, a 1,3-diether compound not having a fluorene structure, and diethyl diisopropylsuccinate, a succinic acid diester compound, were used, and a solid catalyst component for olefin polymerization was prepared by the following method. (i) Into a 500 mL flask equipped with a stirrer and purged with nitrogen gas, 20 g (174.8 mmol) of diethoxymagnesium and 110.0 mL of toluene were placed to form a suspension. (ii) Next, 40.0 mL (365 mmol) of titanium tetrachloride was added to obtain a liquid containing an initial contact product. (iii) While the temperature of the initial contact product-containing liquid was rising, 6.0 mL (22.4 mmol) of diethyl diisopropylsuccinate was added, and the temperature was further raised to 100° C., and the reaction was carried out for 90 minutes while maintaining the temperature. After the reaction was completed, the supernatant was removed, and the reaction product, the first contact product, was washed four times with 105 mL of toluene at 90° C. (iv) Next, 60 mL (547 mmol) of titanium tetrachloride was added to the first contact product, and while the temperature was rising, 1.4 mL (5.6 mmol) of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane was added. The temperature was further raised to 115°C and the reaction was carried out for 60 minutes. After completion of the reaction, the supernatant was removed, and the second contact product, which was the reaction product, was washed twice with 105 mL of toluene at 90°C to obtain a final contact product. Next, the resulting final contact product was washed six times with 100 mL of n-heptane at 40° C., and the solid and liquid were separated to obtain a solid catalyst component (solid catalyst component for olefin polymerization). The solid-liquid separation of the solid catalyst component obtained was carried out, and the titanium content, 1,3-diether content, and succinic acid diester compound content in the solid fraction obtained were measured, and were 3.2 mass%, 3.3 mass%, and 15.8 mass%, respectively. The total content of the 1,3-diether content and the succinic acid diester compound was 19.1 mass%. The molar ratio of the succinic acid diester compound content / titanium content was 0.92. The molar ratio of the 1,3-diether content / succinic acid diester compound content was 0.25. The total pore volume of the solid catalyst component with a diameter of 1 μm or less measured by mercury intrusion porosimetry was 0.4 cm 3 / g, and the specific surface area is 330m 2 / g. The properties of the obtained solid catalyst component are shown in Tables 1 to 3.

[0149] The titanium content in the solid catalyst component, the content of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane corresponding to the 1,3-diether compound having no fluorene structure, which is an internal electron donor compound, and the content of diisopropyl succinate corresponding to the succinic acid diester compound, as well as physical properties, were measured by the following methods.

[0150] <Titanium content in solid catalyst component> The titanium content in the solid catalyst component was measured based on the method of JIS 8311-1997.

[0151] <Internal electron donating compound content> The content of the internal electron donor compound was determined by measurement under the following conditions using a gas chromatograph (GC-14B, manufactured by Shimadzu Corporation). The number of moles of the internal electron donor compound was determined from the results of gas chromatographic measurement using a calibration curve previously measured at known concentrations. (Measurement conditions) Column: Packed column (φ2.6×2.1m, Silicone SE-30 10%, Chromosorb WAW DMCS 80 / 100, GL Sciences, Inc.) Detector: FID (Flame Ionization Detector) Carrier gas: Helium, flow rate 40mL / min Measurement temperature: vaporizer 280℃, column 225℃, detector 280℃

[0152] 2. Formation of polymerization catalyst and polymerization reaction A polymerization catalyst was prepared by charging 1.32 mmol of triethylaluminum, 0.131 mmol of diisopropyldimethoxysilane (DIPDMSi) and 0.00264 mmol of the above solid catalyst component in terms of titanium atom into a 2.0 L capacity autoclave equipped with a stirrer and purged with nitrogen gas. Then, 6.0 L of hydrogen gas and 1.4 L of liquefied propylene were charged, and preliminary polymerization was carried out at 20°C for 5 minutes, followed by heating and polymerization reaction at 70°C for 1 hour. The polymerization activity per 1 g of the solid catalyst component, the melt flowability of the polymer (melt flow rate (MFR)), the proportion of p-xylene solubles in the polymer (XS), the flexural modulus of the polymer (FM), the proportion of oriented layers in the cross section of the injection-molded plate made of the obtained polymer, and the molecular weight distribution of the polymer (Mw / Mn and Mz / Mw) were measured by the following methods. The results are shown in Table 2.

[0153] <Polymerization activity per 1g of solid catalyst component> The polymerization activity per 1 g of the solid catalyst component was calculated according to the following formula (7). Polymerization activity (g / g-cat) = mass of polymer (g) / mass of solid catalyst component (g) (7)

[0154] <Polymer melt flow property (MFR)> The melt flow rate (MFR) (g / 10 min), which indicates the melt flowability of a polymer, was measured in accordance with ASTM D 1238 and JIS K 7210.

[0155] <Ratio of p-xylene solubles in polymer (XS)> In a flask equipped with a stirrer, 4.0 g of a polymer (polypropylene) and 200 mL of p-xylene were charged. Next, the external temperature was set to about 150°C, and stirring was continued for 2 hours while maintaining reflux of p-xylene (boiling point 137-138°C) in the flask to dissolve the polymer. Thereafter, the solution was cooled to a liquid temperature of 23°C over 1 hour, and insoluble and soluble components were separated by filtration. The solution of the soluble components was collected, and p-xylene was distilled off by heating and drying under reduced pressure. The weight of the residue obtained was determined, and the relative proportion (mass%) to the produced polymer (polypropylene) was calculated to be the xylene soluble component (XS).

[0156] <Flexural modulus of polymer (FM)> Using Nissei Plastic Industrial Co., Ltd.'s NEX30III3EG, injection-molded test pieces with a thickness of 4.0 mm, width of 10.0 mm, and length of 80 mm were prepared under conditions of a molding temperature of 200°C and a mold temperature of 40°C, and measurements were carried out at an ambient temperature of 23°C according to JIS K7171.

[0157] <Proportion of oriented layer in cross section of injection molded polymer plate> 1. Formation of molded products According to JIS K 7152-1 and JIS K 6921-2, an olefin polymer was injection molded under the following conditions to obtain a molded article having the external shape shown in FIG. Equipment: NEX-III-3EG manufactured by Nissei Plastics Co., Ltd. Type of test piece: Multipurpose test piece type A1 as specified in JIS K 7139 Resin melting temperature: 200℃ Mold temperature: 40℃ Injection speed: 180mm / sec Holding pressure: 50MPa - 40 seconds 2. Preparation of measurement samples (thin sections for polarizing microscope observation) (1) As shown in FIG. 1, the obtained molded product was cut in a direction perpendicular to the resin traveling direction MD at a position c1, which was approximately 2 cm long from the gate G in the resin traveling direction MD, to obtain a cut product S1 shown in FIG. 2(a). (2) As shown in FIG. 2(a), the cut product S1 obtained in (1) was cut in the center (position c2) parallel to the resin traveling direction MD to obtain the cut product S2 shown in FIG. 2(b). (3) As shown in FIG. 2(b), using a rotary microtome device (RX-860 manufactured by Yamato Kogyo Co., Ltd.), the cut piece S2 was cut out at position c3 parallel to the resin traveling direction MD to a thickness of 30 μm to obtain a thin-section measurement sample S3 shown in FIG. 2(c). (4) Figure 2(d) is a schematic diagram showing the obtained flake-shaped measurement sample S3, in which the left side of Figure 2(d) is a side view of the thin flake-shaped measurement sample S3 corresponding to Figure 2(c), and the right side of Figure 2(d) is a front view of the thin flake-shaped measurement sample S4. 3. Polarizing Microscope Observation FIG. 3 is an enlarged front view of the thin-film measurement sample S3 shown in the right diagram of FIG. 2(d). The above measurement sample S3 was observed with a polarizing microscope (EPCLIPSE LV-100NDA manufactured by NIKON CORPORATION) to identify the core layer c and the orientation layers h1 and h2. The thickness of the core layer was Tc, the thickness of the orientation layers was Th1 and Th2, and the ratio F (%) of the orientation layer to the thickness of the molded layer was calculated using the following formula (6). F(%)=((Th1+Th2) / (Th1+Tc+Th2))×100 (6) The thickness Tc of the core layer and the thicknesses Th1 and Th2 of the alignment layers were calculated by measuring the thickness of the core layer c and the thicknesses of the alignment layers h1 and h2 at any 10 points of the measurement sample S3 and using the arithmetic average values.

[0158] <Polymer elution rate at high temperatures (CFC)> The amount of elution of each molecular weight of polymer at high temperatures was measured using a cross fractionation chromatograph (CFC) (manufactured by Polymer Char) under the following conditions, and the ratio of the total amount of olefin polymers eluting at 120°C or higher to the total amount of olefin polymers (the ratio of the amount of o-dichlorobenzene insoluble at a measurement temperature of 120°C or higher to the total amount of polymers) was calculated. Furthermore, the content of olefin polymers having a molecular weight of 1 million or more in the total amount of olefin polymers eluting at 120°C or higher was calculated. Solvent: o-dichlorobenzene (ODCB) Column: Shodex GPC UT-806M Sample concentration: 5g / L-ODCB Sample volume: 0.5mL Pump flow rate: 1.0mL / min Crystallization rate: 1.0℃(SEC) / min Measurement temperature range: 40 to 140°C (SEC) Flow rate: 1.0mL / min Measurement range: 40℃~140℃

[0159] <Polymer molecular weight distribution> The molecular weight distribution of the polymer was evaluated by the ratio Mw / Mn of the mass average molecular weight Mw to the number average molecular weight Mn and the ratio Mz / Mw of the Z average molecular weight Mz to the mass average molecular weight Mw, which were measured by gel permeation chromatography (GPC) (GPCV2000 manufactured by Waters) under the following conditions. Solvent: o-dichlorobenzene (ODCB) Temperature: 140℃ (SEC) Column: Shodex GPC UT-806M Sample concentration: 1g / liter-ODCB (50mg / 50mL-ODCB) Injection volume: 0.5mL Flow rate: 1.0mL / min

[0160] (Examples 2 to 4 and Comparative Examples 1 to 6) The same procedure as in Example 1 was carried out except that the conditions were as shown in Table 1. The results are shown in Tables 1 to 3.

[0161] [Table 1]

[0162] [Table 2]

[0163] [Table 3] [Industrial Applicability]

[0164] According to the present invention, there can be provided a solid catalyst component for olefin polymerization which contains an internal electron donor compound other than a phthalate ester, has excellent melt flowability and high rigidity, and is capable of producing a polymer with a small amount of low molecular weight polymer.

Claims

1. The present invention includes a 1,3-diether compound and a succinic acid diester compound that are free of magnesium, titanium, halogen, and a fluorene structure, the total content of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound in the total amount of components is 13.0% by mass or more, calculated as a solid content; a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound in the total amount of components to the molar amount (T) of the titanium in the total amount of components is 0.71 to 1.30; a molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure in the total amount of components relative to the molar amount (S) of the succinic acid diester compound in the total amount of components is 0.10 to 0.70; The total pore volume of pores with a diameter of 1 μm or less measured by mercury intrusion porosimetry is 0.3 to 1.0 cm 3 / g, and the specific surface area is 200 m 2 / g or more; A solid catalyst component for olefin polymerization, comprising:

2. The 1,3-diether compound not having a fluorene structure is represented by the following general formula (1): R 1 -O-CH 2 -CR 2 R 3 -CH 2 -O-R 4 (1) (In the formula, R 2 and R 3 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group or a cycloalkenyl group having 3 to 12 carbon atoms, an aromatic hydrocarbon group or a halogen-substituted aromatic hydrocarbon group having 6 to 12 carbon atoms, an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent, an alkylamino group having 1 to 12 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms. 2 and R 3 may be the same or different. 2 and R 3 may be bonded to each other to form a ring. 1 and R 4 R represents an alkyl group having 1 to 12 carbon atoms, a vinyl group, an alkenyl group having 3 to 12 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, a halogen-substituted aromatic hydrocarbon group, or an aromatic hydrocarbon group having 7 to 12 carbon atoms and having a substituent. 1 and R 4 may be the same or different.) 2. The solid catalyst component for olefin polymerization according to claim 1, wherein the 1,3-diether compound is one or more selected from the group consisting of 1,3-diether compounds represented by the following formula (1):

3. The succinic acid diester compound is represented by the following general formula (2): R 5 -O-C(=O)-CHR 6 CHR 7 -C(=O)-O-R 8 (2) (In the formula, R 6 and R 7 are hydrogen atoms or alkyl groups having 1 to 4 carbon atoms, and may be the same or different; R 5 and R 8 are straight chain or branched alkyl groups having 2 to 4 carbon atoms and may be the same or different.

2. The solid catalyst component for olefin polymerization according to claim 1, wherein the catalyst component is one or more compounds selected from the group consisting of compounds represented by the formula:

4. A method for producing the solid catalyst component for olefin polymerization according to any one of claims 1 to 3, comprising contacting a dialkoxymagnesium, a titanium halogen compound, a 1,3-diether compound having no fluorene structure, and a succinic acid diester compound with each other, contacting the dialkoxymagnesium with the titanium halide compound multiple times; When the dialkoxymagnesium is initially contacted with the titanium halide compound, the amount of the titanium halide compound contacted is 1.5 to 10.0 moles per 1.0 mole of the dialkoxymagnesium; the total amount of the titanium halide compound used is 5.0 to 18.0 moles per 1.0 mole of the dialkoxymagnesium; the total molar amount of the 1,3-diether compound not having a fluorene structure and the succinic acid diester compound is 0.10 to 0.20 mol per 1.0 mol of the dialkoxymagnesium, a molar ratio (S / T) represented by the molar amount (S) of the succinic acid diester compound to the total molar amount (T) of the titanium halide compound is 0.020 to 0.040; a molar ratio (E / S) represented by the molar amount (E) of the 1,3-diether compound not having a fluorene structure to the molar amount (S) of the succinic acid diester compound is 0.50 or less; The dialkoxymagnesium is composed of secondary particles which are an aggregate of primary particles having an average particle diameter of less than 2 μm, and has a specific surface area of ​​10 m 2 / g or more 50m 2 / g or less, and the particle size distribution index (SPAN) is 1.30 or less; A method for producing a solid catalyst component for olefin polymerization, comprising the steps of:

5. (I) a solid catalyst component for olefin polymerization according to any one of claims 1 to 3, and (II) The following general formula (3): R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p is 0<p≦3, R 9 When there are multiple R 9 may be the same or different, and when there are multiple Qs, each Q may be the same or different. An organoaluminum compound represented by the formula: A catalyst for olefin polymerization comprising:

6. (I) The solid catalyst component for olefin polymerization according to any one of claims 1 to 3, (II) The following general formula (3): R 9 p AlQ 3-p (3) (In the formula, R 9 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, p is 0<p≦3, R 9 When there are multiple R 9 may be the same or different, and when there are multiple Qs, each Q may be the same or different. and an organoaluminum compound represented by (III) External electron donor compound The catalyst for olefin polymerization according to claim 5, comprising

7. A method for producing olefin polymers, comprising carrying out polymerization of olefins using the olefin polymerization catalyst according to claim 5 or 6.

Citation Information

Patent Citations

  • Ingredient and catalyst for olefin polymerization

    JP1982063310A